PELAKSANAAN PENIMBANGAN DALAM JUAL BELI BUAH KELAPA SAWIT DALAM TINJAUAN HUKUM POSITIF DAN FIQH MUAMALAH (Studi Kasus di Nagari Talao Sungai Kunyit Kecamatan Sangir Balai Janggo Kabupaten Solok Selatan) - Randi Yohari; Eficandra Eficandra; Afrian Raus (Institut Agama Islam Negeri Batusangkar, 2021)
This study aims to explain the implementation of weighing oil palm fruit in Nagari Talao Sungai Kunyit in terms of positive law and fiqh muamalah. This research is a field research. Data were obtained in two ways, namely secondary data and primary data. The primary data are toke (collectors), oil palm farmers and the Head of the Cooperative and Industry Office of South Solok Regency, while the secondary data sources are the profile of Nagari Talao Sungai Kunyit, Nagari year-end reports and Indonesian legislation. This study found that the implementation of weighing in the sale and purchase of oil palm fruit in Nagari Talao was carried out with containers made of wood that were rarely arranged, so that many “brondol” (small) palm fruit fell. Oil palm fruit that falls from the container is not counted in the scales, as a result of farmers' losses. In fact, the number of “brondol” (small) palm oil that has fallen is quite a lot. In positive law, the implementation of weighing selling oil palm fruit in Nagari Talao is not in accordance with the provisions of Article 25 and Article 28 of Law Number 2 of 1981 concerning Legal Metrology, Article 2 of the Minister of Home Affairs Number 68 of 2018 concerning UTTP Calibration and Re-calibration and Article 8 of Law -Law Number 8 of 1999 concerning Consumer Protection. In this explanation, it is explained that the weighing in buying and selling will not harm either party and the scales used must be recalibrated once a year. As for the implementation of fiqh muamalah muamalah in Islam, namely injustice to fellow humans, and there is no fraud (gharar) and elements of coercion (al-ikrah).